Did EGRET detect distant supernova remnants? - Torres, Diego F. (2004)
It might be thought that supernova remnants (SNRs) more distant than a few kiloparsec from Earth could not have been detected by the high-energy c-ray experiment EGRET on board of NASA s Compton Gamma-Ray Observatory. This work analyzes the observational status of this statement in the light of new CO studies of SNRs.